2007
DOI: 10.1182/blood-2006-10-054940
|View full text |Cite
|
Sign up to set email alerts
|

The JAK2 617V>F mutation triggers erythropoietin hypersensitivity and terminal erythroid amplification in primary cells from patients with polycythemia vera

Abstract: The JAK2 617V>F mutation is frequent in polycythemia vera (PV) and essential thrombocythemia (ET). Using quantitative polymerase chain reaction (PCR), we found that high levels of JAK2 617V>F in PV correlate with increased granulocytes and high levels of hemoglobin and endogenous erythroid colony formation. We detected normal progenitors and those that were heterozygous or homozygous for the mutation by genotyping ET and PV clonal immature and committed progenitors. In PV patients, we distinguished homozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
166
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(184 citation statements)
references
References 27 publications
15
166
3
Order By: Relevance
“…The relationship of JAK2 V617F and erythrocytosis, the defining feature of PV, is supported by the observation of heightened erythropoietin sensitivity of homozygous V617F clones compared to heterozygous V617F clones (20), by higher hemoglobin concentrations in JAK2 V617F positive compared to JAK2 V617F-negative ET patients (21), by mouse gene transfection experiments (8) and more recently by the identification of JAK2 exon 12 lesions, which associate primarily with an erythrocytosis phenotype in both man and the mouse(10).…”
Section: Discussionmentioning
confidence: 94%
“…The relationship of JAK2 V617F and erythrocytosis, the defining feature of PV, is supported by the observation of heightened erythropoietin sensitivity of homozygous V617F clones compared to heterozygous V617F clones (20), by higher hemoglobin concentrations in JAK2 V617F positive compared to JAK2 V617F-negative ET patients (21), by mouse gene transfection experiments (8) and more recently by the identification of JAK2 exon 12 lesions, which associate primarily with an erythrocytosis phenotype in both man and the mouse(10).…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, a stable mutational load over 50% or a progressive increase of granulocytic JAK2V617F would reflect the dominance of a JAK2V617F-positive clone over normal progenitors, while an unexplained decrease of granulocytic JAK2V6127F would mark the expansion of a JAK2V617F-negative clone. A major criticism to this hypothesis comes from the observation that the mutational load in granulocytes does not correlate with the mutational load in hematopoietic progenitors, since JAK2V617F-positive progenitors have a greater capacity for differentiation than normal progenitors [25,27]. This observation limits the value of a single determination of JAK2V617F as a prognostic factor or as a surrogate for clonal dominance.…”
Section: Discussionmentioning
confidence: 99%
“…18 Furthermore, the in vivo terminal expansion we demonstrate entirely corroborates the results in murine models [12][13][14] and human MPNs in vitro, where PV and ET patients demonstrated erythroid expansion compared with normal controls after long-term CD34 ϩ cell culture experiments. 19 We also demonstrate, using a novel PCR-based assay, that in individual patients the JAK2 V617F homozygous clone has a competitive advantage over the heterozygous clone and that the heterozygous clone does not significantly expand in vivo. Recent animal models have suggested that gene dosage of JAK2 V617F determines disease phenotype, with higher expression associated with PV and lower expression with an ET phenotype.…”
Section: Resultsmentioning
confidence: 99%